Hubungan Sikap Petugas Kesehatan Dengan Kepuasan Pasien Di Poli KIA UPTD Puskesmas I Denpasar Timur - Darmayanti, Ni Luh Putu Lili (STIKES ADVAITA MEDIKA TABANAN, 2024)
Background: The high maternal mortality rate (MMR) indicates that maternal and child health (KIA) services must be improved. Applying a positive attitude to all patients is a way that health workers can increase patient satisfaction so that patients are interested in undergoing antenatal care to reduce MMR. Objective: This study aims to determine the relationship between the attitude of health workers and patient satisfaction at the Maternal and Child Health Polytechnic (KIA) UPTD Puskesmas I East Denpasar Method: This research uses a correlation analytical design with a cross-sectional study approach. Sampling used a non-probability sampling technique, namely consecutive sampling. The sample used was 172 respondents and the instrument used was a questionnaire. Results: The results of the study showed that of the 172 respondents, the majority of respondents, namely 94 (54.7%) stated that the attitude of health workers was in the positive category and the majority of respondents, namely 90 (52.3%) stated that they were satisfied with the services provided by health workers. The results of the Spearman Rho test show that there is a significant relationship between the attitude of health workers and patient satisfaction, with a p-value <0.001 Conclusion: The more positive the health worker's attitude, the more satisfied the patient. So it is hoped that health workers can apply a friendly attitude, be polite and have empathy for all patients in order to increase patient satisfaction and reduce MMR